If You’re Ready, I Am Ready (But the Wait Is Harming Us Both) Individual Risks in Institutional Conversions - McGarrah Sharp, Mindy (Pastoral psychology, 2020)
Rambo, Adele, and a religion professor walk into a coffee shop. What in the world do they have in common? This essay integrates Lewis Rambo’s scholarship on conversion with pop singer Adele’s popular song “Send My Love to Your Lover” to understand and redress inequity in individual risk within processes of institutional conversion. The author focuses on practices of inclusion in institutions of higher education using the specific example of theological schools with aspirational school mission statements that embrace equity and diversities. She argues that bringing Rambo and Adele into conversation with anecdotal and published research on institutional (in)justice illuminates four practices that institutions could adopt to better align practice with promise and thereby promote wellness for all who are impacted by institutional health.